GrowLab: The effect of augmented reality-based learning on secondary school students’ critical thinking skills in plant structure instruction - Lidiastuti, Arinda Eka; Priyanti, Novie Ary; Arsyad, M.; Shobirin, Achmad (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
Plant growth is fundamental to understanding biological systems, particularly at the secondary school level. Learning about plant structure is a crucial component of biology education; however, many students find this topic challenging because it is often perceived as abstract. Augmented Reality (AR) technology offers an opportunity to enhance learning experiences by enabling interactive three-dimensional visualizations of plant structures. This study investigates the effect of AR-based GrowLab learning on students’ critical thinking skills in the context of plant structure instruction. A quasi-experimental design was employed involving 142 Grade XII secondary school students in Malang. Critical thinking skills were assessed using essay-based test instruments. Data were analyzed using an ANCOVA test with SPSS version 29. The results indicated that AR-based GrowLab learning had a significant effect on students’ critical thinking skills in teaching plant structure (sig < 0.05). The study concludes that AR positively affected learning, particularly in understanding plant growth and structure. Furthermore, the findings suggest that augmented reality should be integrated with pedagogical approaches such as problem-based learning (PBL) to maximize its effectiveness in enhancing students’ critical thinking skills.